2022
DOI: 10.3389/fnut.2022.853565
|View full text |Cite
|
Sign up to set email alerts
|

Food Intake and Diet Quality of Pregnant Women in China During the COVID-19 Pandemic: A National Cross-Sectional Study

Abstract: Background:Between January and April 2020, China implemented differentiated prevention and control strategies across the country, based on the severity of the COVID-19 epidemic/pandemic in different regions. These strategies included lockdowns, social distancing, and the closure of public places. These measures may have affected dietary intake to varying degrees. This study aimed to assess variations in food intake and diet quality among pregnant women according to regional severity and related control measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…Results from the previous studies regarding anxiety and depression are not consistent. Higher anxiety and depression scores were associated with increase in unhealthy foods intake in some studies ( 27 , 45 ), increased intake of both healthy and unhealthy foods in one study ( 59 ), and restrained eating in another study ( 60 ). Stress-related eating can result in a paradox, in which there is an inconsistent direction of association between stress and eating.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Results from the previous studies regarding anxiety and depression are not consistent. Higher anxiety and depression scores were associated with increase in unhealthy foods intake in some studies ( 27 , 45 ), increased intake of both healthy and unhealthy foods in one study ( 59 ), and restrained eating in another study ( 60 ). Stress-related eating can result in a paradox, in which there is an inconsistent direction of association between stress and eating.…”
Section: Discussionmentioning
confidence: 94%
“…Higher emotional eating was associated with increased consumption of cereals and oil, and decreased intake of fish and seafood ( 26 ). Diet quality of pregnant individuals was also associated with the severity of the pandemic conditions in another Chinese study ( 27 ). According to a cross-national study, approximately one third of the pregnant individuals reported that the pandemic had at least moderately impacted their diet.…”
Section: Introductionmentioning
confidence: 95%
“…The Authors reported that a median daily intake of so-called functional food, like vegetables and fruit, significantly decreased to low, moderate, and high severity of pandemic, and, in this sense making immune system more vulnerable. In addition to the low quality of the foods consumed, the perinatal outcomes got worse [ 101 ]. Interestingly, researchers in Northern New England have proposed a model to identify and address questionable food choices among pregnant women during the pandemic period, highlighting the need for specific food programs [ 107 ].…”
Section: Nutrition In Pregnancy During Covid-19 Infectionmentioning
confidence: 99%
“…A sample of 452 postpartum women, from 19 hospitals in 19 provinces/municipalities distributed across seven geographical regions, was enrolled into our research. Speci c sampling methods have been reported on previous surveys [19].…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…Classi cation of COVID-19 pandemic severity COVID-19 pandemic severity was classi ed as low, moderate, high severity and Hubei Province based on the cumulative number of con rmed cases reported on the o cial website of the health commission of each province/municipality by February 29, 2020. The pandemic severity was classi ed as low if less than 100 laboratory con rmed cases were reported, as de ned in our previous study [19]. The pandemic severity was de ned as moderate or high, when 100 to 1000 or more than 1000 laboratory con rmed cases were reported, respectively.…”
Section: Study Design and Participantsmentioning
confidence: 99%